IMPLEMENTASI BUSINESS TO BUSINESS (B2B) DAN GO TO MARKET STRATEGY PADA PENGEMBANGAN APLIKASI AMBUTRACK - Rizka Sulistyoningsih (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2024)
The importance of quick response in health emergency situations has driven innovation in rapid ambulance call systems. This article discusses the implementation of a B2B business model and Go To Market Strategy in the development of the AmbuTrack application, aimed at analyzing effective strategy implementation to enhance the marketing success and business growth of ambulance services through the AmbuTrack application. This application is designed to closely collaborate with hospitals, facilitating scheduling management and introducing responsive ambulance services. By combining information technology approaches with the latest health management practices, this application not only supports hospital scheduling management but also provides a data-based platform for performance analysis and better decision-making. By minimizing administrative barriers, such as application fees typically imposed by hospital staff and ambulance drivers, this solution aims to optimize financial and human resources, creating a more responsive health ecosystem